Crisis and political imbalance during the Fujimori regime. The role of the political caricature. 1998-2000 - Infante Yupanqui, Carlos Rodrigo (2024)
This article examines the role of Peruvian political caricature during the crisis of the Fujimori administration (1998-2000). The research also develops an approach to  the connections between caricature and power. This reading, which links macro and micro sociology, is made from the processes of political imbalance of the Fujimori regime, a process that marked, at the same time, a moment of inflection within the political sphere and that reached the caricature, both officious and opposition. Following a qualitative approach with an interpretative perspective, the analysis includes a contextual reading of some caricatures by important Peruvian graphic humorists. As a result, we find that the opposition caricature played a critical role, characterized by the development of its erosive capacity; the same did not happen with the officious caricature that leaned towards a more functional role to the hegemonic power.